Estratégias comunicacionais no contexto de crise: os contratos de comunicação da Petrobras, O Globo e Planalto em mídias digitais - Machado, Jones (2016)
In a crisis context, in which the facts visibility increases, communication has an even more important function, in the sense of contribution to the reputation of organizations. In the presence of this conjuncture, this study has as theme the strategies of crisis comunication and it delimits to analyze the contracts of comunication established by an organization, by an political institution and by an mean of communication, tensing the choices of each one to deal with the same event in a scenery of mediatic hyper visibility. We elected, as study objects, an brazilian company Petrobras; an political institution - Palácio do Planalto; and an brazilian media institution - O Globo. As empirical objects of study, we selected the blog Fatos e Dados, of Petrobras; the Blog do Noblat, of O Globo, and the blog of Planalto, of the Presidency of the Republic. The corpus of the study, colected between the months of January and December of 2015, is composed by digital institutional posts and publications, referring to the developments of the Parliamentary Commission of Inquiry of Petrobras and of the Operação Lava Jato (in portuguese), which originated the actual crisis of the Company and impacted in the political and economic crisis that Brazil is facing nowadays. The problematic of this research aims to answer the question: ''In which way it is established the communication contracts signed by the organizational, mediatic and political fields in digital media in a crisis context?''. The general objective refers to analyze the communication contracts of a mediatic field representative, a political field representative and an organizational field representative in a crisis moment. In relation to the specific objectives, we seek: 1) Map out, in the digital media selected to the study, the principal moments of Petrobras's crisis addressed in the posts; 2) Verify the comunicative strategies undertaken by Petrobras, by O Globo and by Palácio do Planalto in these moments in their blogs; and 3) Tensing the strategies of the mediatic, political and organizational fields, engaged in these digital media. The research methodological process refers to an triangulation of methods and technics composed by: Case study; Bibliographic research; Non-participative covert observation; Communication contract analysis; and In-depth interview. As research results, we infer that the communicative and discursive strategies of the publications of the organizational, political and mediatic fields have distinct focus, according to objectives and interests of each one. The Petrobras, aiming to decrease the facts and for the business survival, emphasizes the commitment to the investigation's transparency and gives visibility to the actions daily undertaken. In another hand, we infer that mediatic field explores the event, highlighting in its news, the image and credibility crisis, attributing to it the condition of the greatest crisis in Petrobras history. The Planalto though, adopts a defense position exulting the Company possibilities and the importance of investigation of the corruption acts that involves people linked to the Company. In this way, each social field determines a comunication contract, from the recognition of internal and external conditions in which the communicational act is effected, operating choices and undertaken comunicative and discursive strategies, aiming the maintenance and fortification of its legitimacy in the social space.